2013
DOI: 10.1007/s00216-013-7433-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the matrix effect and the physicochemical properties of analytes in gas chromatography

Abstract: The phenomenon "matrix-induced chromatographic response enhancement" (matrix effect) causes quantitative errors in gas chromatography (GC) analyses. This effect varies according to the analyte nature, matrix type and concentration, and GC-system parameters. By focusing on the physicochemical properties of analytes, a predictive model was developed for the matrix effect using quantitative structure-property relationships. Experimental values of the matrix effect were determined for 58 compounds in a serum extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Based on the results of the method validation, the deviation resulting from the analytical method was excluded, and the ME was considered to be the primary cause of the error in the GC/MS analysis. Although the ME is related to the GC/MS system, analyte nature, matrix type, and the concentration of the analyte, its underlying mechanisms are not completely understood 14,26 . In our study, the possible reasons were as follows.…”
Section: Resultsmentioning
confidence: 90%
“…Based on the results of the method validation, the deviation resulting from the analytical method was excluded, and the ME was considered to be the primary cause of the error in the GC/MS analysis. Although the ME is related to the GC/MS system, analyte nature, matrix type, and the concentration of the analyte, its underlying mechanisms are not completely understood 14,26 . In our study, the possible reasons were as follows.…”
Section: Resultsmentioning
confidence: 90%
“…Saka et al. developed a predictive model for the matrix effect in GC analysis using quantitative structure–property relationships . They concluded that increases in molecular polarity (particularly H‐bond donors) and the volume of the analyte increase the matrix effect, while hydrophobicity and an increasing number of nonpolar carbon atoms in the analyte decrease the matrix effect.…”
Section: Resultsmentioning
confidence: 99%
“…Both polarity and stability of a compound would be important factors influencing the degree of response enhancement caused by the matrix-like effect. It has been shown that highly polar compounds, such as organophosphates, have a high adsorption interaction potential with active sites, and a fraction of these decompose in Information Table S3) Note: All tested solutions contained all four IS candidates at the same concentration as the evaluated pesticide (0.05 or 0.5 μg mL −1 each) model for the matrix effect in GC analysis using quantitative structure-property relationships [30]. They concluded that increases in molecular polarity (particularly H-bond donors) and the volume of the analyte increase the matrix effect, while hydrophobicity and an increasing number of nonpolar carbon atoms in the analyte decrease the matrix effect.…”
Section: Compoundsmentioning
confidence: 99%
“…were compared . The relationship between the matrix effects and physicochemical properties was investigated, and it indicated that the molecular polarity and volume of the analyte increase the matrix effect, while hydrophobicity and an increasing number of nonpolar carbon atoms in the analyte decrease the matrix effects . Nevertheless, further research should be performed to clarify the origin and mechanism underlying these matrix effects.…”
Section: Resultsmentioning
confidence: 99%